The Effectiveness of Zero Energy Cool Chamber in Extending the Shelf Life of Cherry Tomatoes with Packaging Treatment - Syahputra, Sufri Yanto; Darmawati, Emmy; Nelwan, Leopold Oscar (PERTETA, 2025)
Cherry tomatoes are of high economic value due to their better nutrition, sweet flavor, and crunchy texture. They are in modern markets due to specific demand and intensive cultivation. Periodic harvesting poses distribution and storage challenges as cherry tomatoes are perishable, leading to price fluctuations and quality deterioration. Temporary storage is required to maintain quality before marketing. Zero Energy Cool Chamber (ZECC) is a low-cost and environmentally friendly cold storage alternative. This study aims to determine the combination of zeolite particle size combined with sand as a cooling medium on the ZECC wall that produces a shelf room temperature according to the temporary storage needs of cherry tomatoes. Cherry tomatoes were stored in retail (250 g) and bulky (1500 g) packaging to assess the effectiveness of the packaging in maintaining quality. Parameters measured included moisture content, texture, color, vitamin C content, and organoleptic. The results showed that chamber 1 (zeolite No. 1 mesh 14-20) was more stable than chamber 2 (zeolite No. 2 mesh 8-16). When loaded, the temperature of chamber 1 ranged from 24.6°C to 27.7°C with RH 94.7% to 95.4%. Retail packaging gave the best results with an organoleptic score of 4.03-4.16 on day 15, higher than the control. The vitamin C content in the retail packaging reached 35.83 mg/100 g, higher than the control (28.94 mg/100 g).